Symptom variability throughout the day in patients with gastroparesis. Issue 2 (28th November 2019) - Shahsavari, Dariush; Yu, Daohai; Jehangir, Asad; Lu, Xiaoning; Zoll, Bryan; Parkman, Henry P.
Abstract: Background: Symptoms of gastroparesis (Gp) can fluctuate at different times of the day. Our aims are (1) To characterize Gp symptom variability throughout the day and in relation to meals and (2) to compare the daily symptom variability in subtypes of Gp—diabetic gastroparesis (DGp) and idiopathic gastroparesis (IGp). Methods: Patients with Gp filled Patient Assessment of Gastrointestinal Symptoms (PAGI‐SYM) and completed a modified GCSI‐DD seven times a day (GCSI‐Throughout the Day [GCSI‐TTD]; before and after meals, and before going to bed) over a 2‐week period. Key Results: A total of 44 patients participated (86% females), including 29 (66%) with IGp, 13 (30%) with DGp, and 2 (4%) with postsurgical Gp. Using the GCSI‐TTD, patients with Gp reported significant postprandial worsening of overall symptom severity, as well as severities of nausea, early satiety, stomach fullness, and abdominal pain. Patients also had progressive worsening of the overall symptom severity, early satiety, stomach fullness, and abdominal pain during the day; however, nausea severity did not differ during the day. Number of vomiting and retching episodes did not show significant variations postprandially or during the day. Patients with IGp had greater symptom severity throughout the day and greater postprandial increase in symptoms compared to patients with DGp. Conclusions and Inferences: Patients with Gp experience postprandial worsening of overall symptom severity, as well as severities of nausea, early satiety, stomach fullness, and abdominal pain. These symptoms also progressively worsen during the day, except for the severity of nausea which persists throughout the day. Understanding the symptom variability in patients with Gp throughout the day and postprandially may be useful in treatment of patients with Gp. Abstract : Symptoms of gastroparesis (Gp) include nausea, vomiting, early satiety, postprandial fullness, and abdominal pain. Background : The severity of these symptoms can fluctuate considerably at different times of the day. Gastroparesis Cardinal Symptom Index (GCSI) evaluated symptoms over 2 weeks, and then, the GCSI‐Daily Diary (GCSI‐DD) was developed, measuring the symptom severity over past 1 day. Patients with Gp often report that their symptoms can vary during the day. Aim : To characterize Gp symptoms variability throughout the day and in relation to meals and to determine the difference of daily symptom variability in diabetic (DGp) and idiopathic (IGp) subtypes of patients with Gp. Methods : Patients with known diagnosis of Gp completed a modified GCSI‐DD which assessed 6 important symptoms of Gp (nausea, retching, vomiting, early satiety, postprandial fullness, and upper abdominal pain) and overall symptom severity seven times a day (before and after meals, and before going to bed) over a 2‐week period. These patients also filled Patient Assessment of Gastrointestinal Symptoms (PAGI‐SYM) at the beginning and the end of the study. Patients were given the option of completing the questionnaires on paper or through a smartphone application (Personal Analytics Companion). Result : A total of 44 patients participated (86% females), including 29 with IGp, 13 with DGp, and 2 with postsurgical Gp. Patients reported a GCSI total score of 2.6 ± 1.1 with postprandial fullness/early satiety (PPF/ES) subscale 3.2 ± 1.4, nausea/vomiting subscale 2.1 ± 1.5, and upper abdominal pain subscale 2.9 ± 1.5. Patients with IGp had a higher baseline GCSI total score and PPF/ES sub‐score compared to patients with DGp (all P < .05). On GCSI‐DD, patients with Gp reported postprandial worsening of overall symptom severity, as well as severities of nausea, early satiety, stomach fullness, and abdominal pain. Patients also had progressive worsening of the overall symptom severity, early satiety, stomach fullness, and abdominal pain during the day; however, nausea severity did not differ during the day. Number of vomiting and retching episodes did not show significant variations postprandially or during the day. Patients with IGp had greater symptom severity throughout the day and greater postprandial increase of symptoms. Conclusion : Patients with Gp experience postprandial worsening of overall symptom severity, as well as severities of nausea, early satiety, stomach fullness, and abdominal pain. These symptoms also progressively worsen during the day, except for the severity nausea which persists throughout the day. Understanding the symptom variability in patients with Gp throughout the day and postprandially may be useful in treatment of patients with Gp.